Pengaruh Penempatan Kerja Terhadap Prestasi Kerja Karyawan Pada PT. FIFGROUP Cabang Manado - Sumanti, Irene Christiani; Rumawas, Wehelmina; Mukuan, Danny D. S. (JURNAL ADMINISTRASI BISNIS (JAB), 2018)
Job Placement is an activity undertaken to decide whether or not an employee is placed in a certain position within a company. Employee performance is a very important thing in the business organization or individual to achieve its goals. This study aims to determine the effect of job placement on employee performance of PT. FIFGROUP Cab. This study aims to determine the effect of job placement on employee performance. The research method used is quantitative associative and data collection is done by survey. Population in this research all work of PT. FIFGROUP Cab. Manado. While the sample using by Slovin in formula and obtained the number of 85 respondents, using simple linear regression test and correlation analysis with SPSS 23.0. Using simple linear correlation and linear regression analysis. The result of R value between the two variables is 0.282 means the relationship between job placement on employee performance is low. Then the value of R Square (coefficient determinant) 0.079. This shows that the employee performance at PT. FIFGROUP Cab. Manado 7.9% is affected by job placement, while 92.1% is determined by other factors not examined in this study. One of the factors that make the job placement does not affect the employee's work performance is website, conditions and rules that have been determined by PT. FIFGROUP Cab Manado does not demand the same educational background as the existing job position or position. To further improve the performance of work then the job placement should be in accordance with existing educational background.Â Keywords: Job Placement, Employee Performances